PENGARUH INTELLECTUAL CAPITAL TERHADAP MARKET PERFORMANCE DIUJI DENGAN MENGGUNAKAN METODE PLS: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI 2008-2012 - Mustofa, Fauzi; Minar Savitri, Dhian Andanarini (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Intellectual capitalis recognizedas a strategic asset that provides acompetitive advantage to the organization for superior performance in themodern era of the knowledge-based economy. This study aimed to examinethe effect of the components of the Intellectual Capital (VAICTM) to marketperformance is proxied by TVA , CAR and MtBV.The Value Added Intellectual Coefficient (VAICTM) methode is used tomeasure ofIntellectual Capital. This study uses data from 120 publicly listedcompanies in Indonesian Stock Exchange between the years 2008 to 2012. Itis an empirical study using Partial Least Square (PLS).The results show that: Intellectual Capital influences positively to marketperformance. Its prove that manufacturing companies in Indonesia have beenmanaging knowledge assets well so its important role in the formation ofadded value and contribute to the improvement of company's marketperformance.